A Compilation of Moored Current Meter Data and Wind Recorder Data from the Severe Environment Surface Moorint (SESMOOR). Volume 43. - Crescenti, Gennaro H.; Tarbell, Susan A.; Weller, Robert A. (1991)
A Severe Environment Surface Mooring (SESMOOR) was designed to make long term meteorological and near surface oceanographic measurements in areas where harsh environmental conditions prevail. SESMOOR was deployed in the North Atlantic Ocean approximately 300 km southeast of Halifax, Nova Scotia for 141 days during the winter of 1988-89. Meteorological data were acquired from two Vector Averaging Wind Recorders (VAWR) located on top of a specially designed buoy mast and included air temperature, relative humidity, barometric pressure, wind velocity, solar and longwave radiation. Sea surface temperature was also acquired by the VAWRs. Current velocities and sea temperatures were obtained from two Vector Measuring Current Meters (VMCM) at 20 and 50 meters below sea surface. This report discusses instrument performance, data quality, pre- and post- deployment calibrations, data telemetry, data processing procedures. This report also presents the data in a variety of displays.